The role of educated organizations in reducing counterfactual behavior: . An exploratory study of the opinions of a sample of teachers in the General Directorate of Education in Babil Governorate - سنان عليوي عباس (Iraqi Journal for Administrative Sciences, 2024)
Objective of the study: The current study seeks to identify the role of educated organizations with their four dimensions (shared vision, leadership, learning, change) in reducing counterproductive work behaviors by their dimensions (personal behavior, organizational behavior). - Population and sample of the study / The study was carried out in the educational sector in a sample of teachers working in schools affiliated to the General Directorate of Education in Babil Governorate, where a sample of respondents was taken, amounting to (135) individuals. - Problem and Questions of the Study/ The study focused on a main problem, which is "Do the educated organizations contribute to reducing the counter-work behavior of teachers in the Babel Education Directorate?" - Contribution and importance of the study / The contribution of the study is to try to reduce the knowledge gap for the variables, as it focused on the role of educated organizations in reducing counterproductive behaviors. The importance of the study lies in that the variables (the learning organization and reverse work behavior) are important variables that directly affect the contemporary educational environment in particular and other organizations in general. - Study methodology and tools / The study adopted the descriptive analytical approach in polling the opinions of respondents to describe and analyze the data of the study and then interpret it to reach practical results that depend on the sample’s answers to the study questions. The data was collected through the questionnaire, which in its paragraphs relied on the standards of previous studies, and the data was analyzed through a group through a number of statistical methods, including (arithmetic mean, standard deviation, Cronbach's alpha, impact factor, coefficient of determination) based on the (SPSS) program. And the program (Excel). - The most important results / The study found a set of results, including the high level of the two main variables, and the study also found that educated organizations lead to the reduction of counterproductive work behaviors in those schools. -The most important recommendations: The surveyed schools should pay attention to building and developing positive behaviors because of their impact on a set of organizational and behavioral outcomes such as organizational creativity, organizational ingenuity, organizational flexibility, job satisfaction, positive behavior, cooperation, and achieving advanced levels of performance.